Patents on Membranes Based on Non-Fluorinated Polymers for Vanadium Redox Flow Batteries - Choi, So-Won; Kim, Tae-Ho; Cha, Sang-Ho (Recent Patents on Nanotechnology, 2017)
Background: Vanadium redox flow batteries (VRFBs) have received considerable attention as large-scale electrochemical energy storage systems. In particular, VRFBs offer a higher power and energy density than other RFBs and mitigate undesirable performance fading, such as inevitable ion crossover, because of the unique advantage that only the vanadium ion is employed as the active species in the two electrolytes. Description: The key constituent of VRFBs is a separator to conduct protons and prevent cross-mixing of the positive and negative electrolytes. For this purpose, ion exchange membranes like sulfonated polymer membranes can be used. Although this type of membrane does not have ion exchange groups, it can achieve an ion exchange capacity by the formation of pores. Conclusion: This review highlights the patents on the preparation of non-fluorinated membranes (sulfonated aromatic polymer membranes and porous membranes) as alternatives to high-cost perfluorinated polymers and their VRFB performance.
Keywords: ion exchange membrane